Mobile Agent Life Cycle Demystified using Formal Method - Agboizebeta Imianvan, Anthony; Oluwole Akinyokun, Charles (Transactions on Engineering and Computing Sciences, 2015)
Underlying technique for mobile agent development is often mystified. Existing research sometimes ignore unveiling the details of the mobility and autonomy of the agent system. This paper exposes using formal methods the technique of a mobile agent system using a life cycle. The system proposed will serve as takeoff springboard for mobile agent developers.